Software-Defined Networking (SDN): the security review. Issue 1 (2nd January 2020) - Hussein, A.; Chadad, Louma; Adalian, Nareg; Chehab, Ali; Elhajj, Imad H.; Kayssi, Ayman
ABSTRACT: The search for better networking paradigms has fostered the emergence of Software Defined Networking (SDN), which allows the decoupling of the data plane from the control plane and to configure the network dynamically. SDN provides network operators with significant visibility and granularity of their networks leading to more flexibility in programming these networks. Typically, with every new technology paradigm, the security concerns represent a serious challenge. In this paper, we provide a comprehensive SDN security review including the different vulnerabilities and attacks that SDN suffers from. The objective is to entice the SDN community to address such issues inherently and not as an afterthought. The paper also reviews the different security proposals that have been presented or implemented for SDN and by SDN. A general discussion is included to shed light on the pending security issues and some proposed solutions are presented.